Anterolateral rupture of popliteal cysts in rheumatoid arthritis. Issue 3 (March 1991) - Kirkham, B; Churchill, M; Dasgupta, B; Wedderburn, L; Spencer, J; Macfarlane, D G
Abstract : Popliteal cysts occur commonly in both normal and arthritic knees. Most cysts are formed by distension of the medially situated semimembranosus bursa. Popliteus bursa distension occurs uncommonly as a lateral popliteal cyst. Two cases of rupture of lateral cysts which produced symptoms related to the anterolateral lower leg are reported. The difficulty of diagnosing the condition because of this unusual site of inflammation and subsequent management problems are discussed.